Conserving Cultural Heritage
1 online resource (354 pages)
Keywords: The third International congress of Science and Technology for the Conservation of Cultural Heritage, TechnoHeritage 2017, was held in Cadiz, from 21 to 24 May 2017, under the umbrella of the TechnoHeritage network. TechnoHeritage is an initiative funded by the Spanish Ministry of Economy and Competitivity dedicated to the creation of a network which integrates CSIC and University groups, private companies and end users such as foundations, museums or institutions. The network’s purpose is to foster the creation of transdisciplinary (and not only multidisciplinary) initiatives focused on the study of all assets, movable or immovable, that make up Cultural Heritage. A high-quality scientific programme was prepared, which includes new emerging topics on Cultural Heritage (1) Nanomaterials and other Products for Conservation, (2) New Technologies for Analysis, Protection and Conservation, (3) 20th Century Cultural Heritage, (4) Significance of Cultural Heritage. Policies for Conservation, (5) Deterioration of Cultural Heritage, (6) Biodeterioration: Fundamentals, Present and Future Perspectives and (7) Underwater Cultural Heritage. A special session "Biodeterioration: Fundamentals, present and future perspectives, a session in honour of Prof. Cesáreo Sáiz Jiménez" took place. Our intention was to recognise the work of Prof. Sáiz Jiménez, who recently retired, and its impact on the Cultural Heritage conservation community, which he has helped to promote through numerous activities including, in 2011, the creation of the TechnoHeritage network. This volume publishes a total of eighty-three contributions which reflect the state of the art investigations on different aspects of cultural heritage conservation.